Mental Health Services and Quality of Life - SVEINBJÖRG J., SVAVARSDÓTTIR (International Journal of Psychosocial Rehabilitation, 2014)
The article examines the self-reported quality of life among people with mental illness in a psychiatric rehabilitation centre in Iceland. Quantitative and qualitative research methods were used and 47 informants were interviewed and their reports analysed. The interaction between services provided and quality of life was examined. The findings indicate that needs are rarely met and disclosure of treatment information is lacking. Informants describe themselves as socially isolated and non-participants in society. Results confirm that people with mental illness want caring and support in their rehabilitation. Meeting needs reveals accelerated recovery and renewed interaction within society.